Autism spectrum conditions in hikikomori: A pilot case–control study. Issue 12 (13th October 2020) - Katsuki, Ryoko; Tateno, Masaru; Kubo, Hiroaki; Kurahara, Keita; Hayakawa, Kohei; Kuwano, Nobuki; Kanba, Shigenobu; Kato, Takahiro A.
Abstract : Aim: Hikikomori, a form of pathological social withdrawal, has been suggested to have comorbidity with autism spectrum disorder (ASD). This study aimed to clarify how characteristics of hikikomori are associated with ASD, including undiagnosed autism spectrum conditions (ASC), in clinical settings. Methods: A total of 416 clinical patients were recruited through the Mood Disorder/Hikikomori Clinic at Kyushu University Hospital. A total of 103 hikikomori cases and 221 clinical controls without hikikomori conditions were extracted using a semi‐structured interview, and completed a series of self‐rated scales, including the Japanese version of the Autism‐Spectrum Quotient (AQ‐J). Results: Compared to non‐ hikikomori controls, hikikomori cases were more likely to have higher autistic tendency based on the AQ‐J. The cases showed more severe subjective depressive symptoms based on the self‐rated Beck Depression Inventory II, whereas no significant difference was found on interview‐based severity evaluation using the Hamilton Depression Rating Scale. Comparison within hikikomori cases based on the AQ‐J cut‐off score revealed that hikikomori cases with high ASC were significantly more likely to have higher traits of modern‐type depression, smaller social networks, and less social support. Conclusion: The present data suggest that hikikomori sufferers are more likely to have autistic tendency, and that hikikomori sufferers with high ASC may have much more difficulty in social communication and social interaction. In addition, those with high ASC may also have lower self‐esteem and higher complaint tendencies as aspects of modern‐type depression traits, which may relate to the occurrence of hikikomori . Thus, evaluating autistic tendencies is important for appropriate interventions in hikikomori . Further investigations should be conducted to validate our pilot findings using structured diagnostic systems of ASD.